Higher accumulation of mitragynine in Mitragyna speciosa (kratom) leaves affected by insect attack - Nisa Leksungnoen; Tushar Andriyas; Rossarin Tansawat; Pichaya Pongchaidacha; Piyawadi Khaoiam; Thanundorn Thanusuwannasak; Chatchai Ngernsaengsaruay; Chawatat Thanoosing; Suwimon Uthairatsamee (PLoS ONE, 2025)
Kratom leaves are widely consumed by locals to increase their stamina for working longer hours in the field. However, insect damage to the leaves can lead to significant loss of leaf harvest. Despite this, there remains considerable uncertainty regarding how herbivory attack affects the chemical composition of kratom’s leaf metabolome. In this study, we investigated the effect of insect herbivory on the secondary metabolites (SMs) of kratom leaves, using untargeted metabolomics as well as the effect on the accumulation of mitragynine and relation to leaf traits. The presence of diverse herbivore species were observed on the kratom leaves as indicated by three orders of insects including Coleoptera (beetles), Lepidoptera (butterflies and moths) and Hemiptera (true bug). A higher accumulation of mitragynine was observed as a defense mechanism against herbivores, with the study also finding a correspondence between increased mitragynine levels and elevated leaf acidity. A significant difference in the presence of three key metabolites (cearoin, 8-hydroxy-8-(3-octyloxiran-2-yl) octanoic acid, and 2,3,5,7-tetramethoxy-9,10-dihydrophenanthrene) that have interesting therapeutic usage, between insect and non-insect leaves, indicated the influence of interaction with insect herbivory. In conclusion, these findings highlight the potential to manage insect herbivory to modulate alkaloid accumulation in kratom, offering a sustainable approach that preserves insect biodiversity while naturally boosting the plant’s chemical defense.